Evaluation of coriander germplasm for yield and powdery mildew resistance - Rao, A K Singh, S S (Journal of Spices and Aromatic Crops, 2016)
An experiment was conducted during rabi to identify coriander lines resistant to powdery mildew and high yield. Twelve entries were included for evaluation with one each of national check as well as local check. The result showed that out of 12, four lines were found susceptible to disease and remaining were moderately resistant. In the present study coriander line Cor-31 (DH220) produced the highest yield 1021.53 kg ha-1 with moderate resistant reaction against powdery mildew. The area under disease progress curve (AUDPC) and apparent rate of infection (r) values were 502.24 and 0.035, respectively.